Arima Forecasting of Indonesia’s Sovereign Sukuk as a Sustainable Financing Instrument - Hartono, Haryani Santo; Nurrachmi, Rininta; Salleh, Sharifah Nabilah Syed (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
Sukuk development in Indonesia, along with SBSN (Surat Berharga Syariah Negara) sovereign securitization sukuk SBSN, sovereign securitization sukuk (SBSN), sustainable and diverse in-structure financing sukuk SBSN, is being balanced with the increasing usage of Sharia-compliant instruments for the financing of fiscal deficits and the management of sovereign debts, which continues to expand. An Autoregressive Integrated Moving Average (ARIMA) model is employed in this study, using monthly time series data for the period 2019 to 2024. Among the time series modeling techniques, ARIMA was chosen because explicit macroeconomic theories are not required for time series projection; thus, it is more suitable for modeling historical time series. The study has found that while the values of outstanding sukuk will no doubt increase, the uncertainty of longer-term forecasting will also increase. Forecasting in the present study lacks immediate quantification; however, the analyses provide a relevant and sustained policy framework for sovereign debt, and the analyses support the potentially strategic role of thematized instruments in fiscal management and for the sustainability of sukuk, in particular, focused sukuk, green sukuk, and retail sukuk. The research outlines strategic considerations for managing Shariah-compliant, long-term, and dynamic debt in Indonesia, thereby aligning financial innovation with national development interests.